Effect of the preparation of lime putties on their properties - Navrátilová, Eva; Tihlaříková, Eva; Neděla, Vilém; Rovnaníková, Pavla; Pavlík, Jaroslav (Scientific reports, 2017)
In the study of lime as the basic component of historical mortars and plasters, four lime putties prepared from various kinds of lime of various granulometry and by various ways of preparation were evaluated. The rheological properties and micro-morphologic changes, growing of calcite crystals, and rate of carbonation were monitored. The lime putty prepared from lump lime achieves the best rheological properties, yield stress 214.7 Pa and plastic viscosity 2.6 Pa·s. The suitability of this lime putty was checked by testing the development of calcium hydroxide and calcite crystals using scanning electron microscopy and environmental scanning electron microscopy. The disordered crystals of calcium hydroxide exhibit better carbonation resulting in the large crystals of calcite; therefore, the mortar prepared from the lump lime has the highest flexural strength and compressive strength 0.8/2.5 MPa, its carbonation is the fastest and exhibits the longest durability. Also, thanks to the micro-morphological characterization of samples in their native state by means of environmental scanning electron microscopy, the new way of lime putty preparation by mixing was proven. The preparation consists in the mechanical crash of the lime particles immediately after hydration. This enables the properties of putty prepared from lump lime to be nearly reached.